Observer-based fault tolerant control and experimental verification for rigid spacecraft - Hu, Qinglei; Zhang, Xinxin; Niu, Guanglin (Aerospace science and technology, 2019)
This work addresses the problem of observer-based closed-loop attitude stabilization in the presence of actuator faults, reaction wheel friction and external disturbances. As a stepping stone, an iterative learning disturbance observer (ILDO) is developed to estimate and compensate for the synthetic disturbances mentioned above. Specially, this ILDO does not need complex faults isolation operations or require knowledge related to these uncertainties. Furthermore, a typical proportional-derivative controller incorporating with the presented ILDO is employed to realize attitude stabilization for spacecraft subject to the actuator failures and uncertainties. The significant feature of the proposed strategy is that the uniformly ultimately bounded stability of the overall closed-loop system with observer-controller architecture could be guaranteed. The effectiveness and robustness of the developed scheme are investigated via a set of numerical simulations and analyses. Particularly, an experimental verification involving a hardware-in-loop platform is further provided to validate the engineering feasibility of the proposed strategy.